A study into shared reading groups, with specific relation to religious reading - Harsh, Esther Valora (Frontiers in Psychology, 2022)
This paper examines a live shared-reading group conducted through The Reader Organization, with the approval of the University of Liverpool's ethics committee. It is a revised excerpt from a successful inter-disciplinary Ph.D. thesis undertaken within the School of Psychology.1 The intention in forming the group was to explore the reading of Marilynne Robinson's Home by a wide variety of modern readers of different backgrounds and persuasions, in the light of religious writing in an age of diminished religious tradition. The main research question was to test what literature can do in carrying meaning which can be seen as religious, or was previously deemed religious, among readers who may not think of themselves in such terms. The second was to see how a shared community-group setting can enable collaborative engagement with the challenge to develop different ways of thinking, beyond the individual default of either religious dogma or anti-religious prejudice. The method employed overall in the wider Ph.D. study was Grounded Theory: essentially, empirical analysis rather than top-down conceptualization. Grounded Theory, in refusing to begin from rigidly preassembled categories, is appropriate to a literature-inflected study and, in particular, a literary study that is concerned with religious meaning in situations of humanitarian crisis. It allows the possibility of empirical work and careful detailed analysis, amid a complex of overlapping psychological, spiritual, and family concerns entangled within the experience of modern life. In this particular case study, which may be described as a form of Action Research, the researcher, also acting as the reader leader of the group, brought developed tools taken from psychologist Wilfred Bion, introduced to the reading group itself during the sessions as a means of measurement and navigation through the novel. If the aim was simply to undertake a study of the text, then this paper would be more narrowly literary, but the concern was with wider real-world effects in relation to individuals within the group work. Through close examination of the week-by-week transcripts of the reading group, this study highlights the search for moments of development, or what might have stood in the way of development. The researcher used a consensus group of three supervisors to check the selection of the best moments (failing or succeeding in coming closer to what will be called below, after Bion, “0”) recorded in the written transcripts of the sessions. One of the most powerful findings in this study is what will be called a mini-tradition developed by the group members in praxis, in terms of practices which they find, use, and come back to during their work with more difficult and painful passages in the text.